ANALISIS KONTRIBUSI DAN POTENSI RETRIBUSI DAERAH - Nurlian Nurlian; Siti Rofingatun; Ivanna K. Wamafma (Universitas Cenderawasih, 2018)
This study aims to analyze the contribution and potential of regional retibusi in terms of the variables of contribution, growth, effectiveness, and performance of regional levies with the source of data in this study sourced from Daeah Government and using descriptive qualitative analysis that is explorative. The results of the study show that the results of the analysis of the contribution of regional retribution are relatively lacking, while the level of effectiveness of collecting local retribution is very effective. So it can be concluded that pelayana health levies are classified as potentially levied because of several types of levies collected only health retribution that meets the criteria of being equal to twenty-five point forty-three percent. Keywords: Contributions and Regional Retribution Potential